Regioselective synthesis of heterocyclic N-sulfonyl amidines from heteroaromatic thioamides and sulfonyl azides - Ilkin, Vladimir; Berseneva, Vera; Beryozkina, Tetyana; Glukhareva, Tatiana; Dianova, Lidia; Dehaen, Wim; Seliverstova, Eugenia; Bakulev, Vasiliy (Beilstein Journal of Organic Chemistry, 2020)
N-Sulfonyl amidines bearing 1,2,3-triazole, isoxazole, thiazole and pyridine substituents were successfully prepared for the first time by reactions of primary, secondary and tertiary heterocyclic thioamides with alkyl- and arylsulfonyl azides. For each type of thioamides a reliable procedure to prepare N-sulfonyl amidines in good yields was found. Reactions of 1-aryl-1,2,3-triazole-4-carbothioamides with azides were shown to be accompanied with a Dimroth rearrangement to form 1-unsubstituted 5-arylamino-1,2,3-triazole-4-N-sulfonylcarbimidamides. 2,5-Dithiocarbamoylpyridine reacts with sulfonyl azides to form a pyridine bearing two sulfonyl amidine groups.
Keywords: amidines; Dimroth rearrangement; isoxazoles; sulfonyl thiazoles; thioamides; 1,2,3-triazoles